Single walled carbon nanotube growth and chirality dependence on catalyst composition - Alvin Orbaek White (Nanoscale, 2013)
Vertical arrays of single walled carbon nanotubes (VA-SWNTs) were grown using bi-metallic nanoparticle pro-catalysts. Iron oxide particles were doped with varying quantities of first row transition metals (Mn, Co, Ni, and Cu) for a comparative study of the growth of nanotubes. VA-CNT samples were verified using scanning electron microscopy, and characterized using resonance Raman spectroscopy. The length of the VA-CNTs is used as a measure of catalyst activity: the presence of dopants results in a change in the CNT length and length distribution. Cross correlation of the Raman spectra reveal variations in the distribution of radial breathing mode peaks according to the pro-catalyst composition. The formation of various chirality nanotubes is constant between repetitive runs with a particular catalyst, but may be controlled by the identity and concentration of the metal dopants within the iron catalyst. These results demonstrate that the composition of the catalyst is a major driving force toward type selective growth of nanotubes.